Capital Aggregation and Optimality Conditions - Whitaker, J. K. (Review of Economic Studies, 1968)
Journal Article Capital Aggregation and Optimality Conditions Get access J. K. Whitaker J. K. Whitaker Bristol University and University of Virginia Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 35, Issue 4, October 1968, Pages 429–442, https://doi.org/10.2307/2296770 Published: 01 October 1968